Correlation between mismatch repair statuses and the prognosis of stage I–IV colorectal cancer - Tong, Guojun; Zhang, Guiyang; Hu, Yan; Xu, Xuting; Wang, Yanyan (Frontiers in Oncology, 2024)
Background: The role of microsatellite instability (MSI) and prognosis for II-III stage colorectal cancer (CRC) has been described, but that of MSI for I and IV CRC is controversial. Methods: A total of 2540 CRC patients were collected from Huzhou Central hospital, China, from January 2006 to 2016 and 783 cases were excluded. This retrospective study illustrates the correlation between MMR status and prognosis for 1757 CRC patients This study illustrates the correlation between MSI and prognosis for CRC patients. Two groups were classified as MSI-H and MSI-L&MSS. If the expression of one or more mismatch repair (MMR) proteins was negative, it was considered microsatellite instability high expression(MSI-H), while the positive expression was microsatellite instability low expression and microsatellite stability (MSI-L&MSS), as assessed by correlation analyses. Overall and disease-free survival were analyzed by Kaplan–Meier method. Univariable and multivariable were assessed by Cox regression analysis. Results: Preoperative serum S-CEA, positive lymph, tumor size, Pathologic tumor(Pt)status, node (N) stage, differentiation, chemotherapy, and the 8th Edition of the American Joint Committee on Cancer (AJCC-8) were significantly correlated with MSI (P=0.028,0.037,0.019,0.007,0.002,<0.001,<0.001,<0.001 respectively), while tumor location was not associated with MSI . Univariable and multivariable analyses showed that MSI was an independent factor for CRC. The 5-year overall survival and 5-year disease-free survival (DFS, P<0.001) rates differed significantly between the two groups in II, III, and IV stages while I stage did not show a significant difference (P>0.05). Conclusions: MSI-H was associated with good prognosis for stages II–IV, while stage I did not show any significant correlation. Moreover, MSI expression was an independent prognostic factor. The scope of the study: Gastrointestinal Cancers: Colorectal Cancer.